Water Quality Assessment of Two Popular Lakes in Yangon, Myanmar - Theingi Ye Myint; Cho Cho Thin Kyi; Phoo Ei Soe; Shwe Yee Mon Mon (IPTEK Journal of Proceedings Series, 2017)
This study aimed to characterize and access the existing water quality of the two popular lakes (Kandawgyi Lake and Innya Lake) in Yangon, Myanmar. The water samples were collected from different locations of the lakes and inlet points of the lakes. The collected samples were analyzed for different physical and chemical parameters such as oxygen demand, nutrient concentrations, solids, and alkalinity. In order to access the state of the lake’s water quality, the samples were compared with standard water quality values. Most of the water quality parameters of the inlet points were found to be above the standard water quality values in both lakes. Biochemical oxygen demand and chemical oxygen demand are also much greater than the limit of the compared standard (especially in inlet drain waters). It was found that continuous polluted water drains from catchment area to main inlets of both lakes. Algae blooming can be seen visually in Kandawgyi Lake , in which water quality is more deteriorated than Innya Lake. This paper will serve as a baseline data which could be used for water quality monitoring and evaluation of the lake.